Near-surface circulation in the southern Gulf of Cádiz - Machín, F.; Pelegrí Llopart,José Luis; Marrero-Díaz, A.; Laiz, I.; Ratsimandresy, A. W. (Deep Sea Research Part II: Topical Studies in Oceanography, 2006)
We have used several data sets (expandable bathythermograph sections, buoy trajectories, current-meter moorings, and surface wind stress) to investigate the temporal variation of the upper-thermocline (North Atlantic Central Waters) circulation patterns in the southern Gulf of Cádiz. The main data set consists of eight expandable bathythermograph sections (two per season) running between the Strait of Gibraltar and Cape Beddouza, just offshore the continental slope and approximately parallel to the Morocco coastline. A salinity–temperature polynomial, obtained from historical conductivity–temperature-depth data, is used to infer dynamic properties (salinity, density, dynamic height, geostrophic velocity and transport). Dynamic heights are calculated referred to the neutral density surface, which we justify is a good reference level for this section. These observations are then combined with a process-oriented, one-layer, quasigeostrophic model for the northeastern corner of the North Atlantic subtropical gyre with modified eastern boundary conditions. The results indicate the existence of about 1 Sv onshore transport all year long into a 300 km long coastal transition zone off Morocco, which must follow south as a narrow current. During winter the flow is zonal towards the slope and recirculates south as a very narrow jet of less than 100 km width. During summer the flow probably becomes more intense but is deflected southeastward before reaching the slope, such that the onshore geostrophic transport into the coastal transition zone decreases and the recirculating band widens.